Något om Oscar Levertin - Lamm, Martin (Nordisk judaistik, 1977)
In this paper, the author first traces the interconnections between two of the oldest Jewish families of Sweden, viz. his own, and that of the noted poet and critic Oscar Levertin (1862-1906). In the rest of the paper two themes in Levertin’s writing are explored. From early manuscripts, written while Levertin still was a high school student, and until the mature poems, short stories and essays he wrote toward the end of this life, the city of Stockholm was one of his major motives. In Levertin’s best short story, "Kalonymos", the Stockholm motive is combined with the second motive explored in this paper, viz. Levertin’s commitment to and identification with the Jewish people and its tragic fate through the ages. Throughout his life Levertin suffered from feelings of alienation, and in his last years he reproached himself for having expressed feelings of hate and vengeance in the Jewish poems of his Legender och visor (1891).